Concussion among male athletes in Iceland : anxiety, depression and stress - Viktor Örn Margeirsson 1994- (2022)
The objective of the study was to examine whether there is a relationship between number of sustained concussions and mental health issues among male athletes in Iceland. The research screened for symptoms of anxiety, depression, and stress. The sample consisted of 366 participants in the age range of 18 to 45 (M = 27.84, SD = 7.14) that were currently playing or had previously played in one of the two top leagues in football, handball, or basketball, in the top league in ice hockey, or in the Icelandic Championship in combat sports in Iceland. The participants answered an online questionnaire including background questions, information regarding their concussion history, and questions regarding their mental health which was used to screen for anxiety (GAD-7), depression (PHQ-9), and stress (PSS). The results indicate that male athletes who reported four or more concussions scored significantly higher on PHQ-9 than those who reported history of none or one concussion. Additionally, the participants which had sustained four or more concussions were more likely to score above the clinical cut-off on PHQ-9 when compared to the participants with no history of concussion. With respect to anxiety (GAD-7), those who reported two to three concussions scored significantly higher than those who had sustained none or one concussion. No significant relationship was found among stress (PSS) and the number of concussions that the participants had sustained. The results indicated that those who had a history of one or more concussions had generally worse mental health than those who had sustained fewer or none. Keywords: concussion, sport-related concussion, mental health, anxiety, depression, stress, athletes